Posthumanizm według Pramoda K. Nayara [Posthumanism According to Pramod K. Nayar] - Hoffmann, Krzysztof (Czas Kultury [Time of Culture], 2014)
An awareness of posthumanism in Polish research was confirmed by the publication of a thematic issue of "Teksty drugie" [Second Texts] on the subject at the beginning of 2013. Publications in the English-speaking world today are now seeking to codify in textbooks the basic assumptions of this stance. The text is an attempt at a critical reading of Pramod K. Nayar’s "Posthumanism", introducing and explaining the specific vocabulary which is used by the author; it also describes the political project for a future interspecies community contained in the book, and questions the weak presence of deconstruction in the list of sources on posthumanism.
https://katalog.adlr.link/Record/ai-53-330314